2017
DOI: 10.3390/nu9060610
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Disparities in Dietary Sodium Intake from Snacking in the US Population

Abstract: Background: The US population consumes dietary sodium well in excess of recommended levels. It is unknown how the contribution of snack foods to sodium intake has changed over time, and whether disparities exist within specific subgroups of the US population. Objective: To examine short and long term trends in the contribution of snack food sources to dietary sodium intake for US adults and children over a 37-year period from 1977 to 2014. Methods: We used data collected from eight nationally representative su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…While these findings are not directly comparable due to different classification systems used for categorizing products, they still highlight a number of key food categories globally that consistently contribute to a large share of sodium purchases. Prior research in Australia and globally has also demonstrated higher sodium intakes in individuals with a lower socio-economic status (SES) [29][30][31][32]. By using contemporary and objectively collected sodium purchase data, representative of Australian households, our findings suggest that differences in sodium consumption according to SES is likely at least partly driven by larger volumes of packaged foods and beverages purchased by lower-income households, rather than due to purchases of higher-sodium content products.…”
Section: Discussionmentioning
confidence: 59%
“…While these findings are not directly comparable due to different classification systems used for categorizing products, they still highlight a number of key food categories globally that consistently contribute to a large share of sodium purchases. Prior research in Australia and globally has also demonstrated higher sodium intakes in individuals with a lower socio-economic status (SES) [29][30][31][32]. By using contemporary and objectively collected sodium purchase data, representative of Australian households, our findings suggest that differences in sodium consumption according to SES is likely at least partly driven by larger volumes of packaged foods and beverages purchased by lower-income households, rather than due to purchases of higher-sodium content products.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, this study does not address why mortality may have increased in recent years, which merits further investigation. Potential explanations may include changes in prevalence, screening methods (blood pressure guidelines changed in 2003 and global) [1], a greater appreciation for the role hypertension plays in facilitating life-threatening comorbidities (physicians may be more likely to indicate hypertension as a underlying cause of death), changes in accuracy of ICD coding over time, antihypertensive medication use, blood pressure control [30], and increased sodium intake [31,32]. Importantly, recent NHANES data have pointed to an overall increase in the burden of hypertension, although control of hypertension has improved [1,30].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research in Australia and globally has also demonstrated higher sodium intakes in individuals with a lower socio-economic status (SES) [29][30][31][32]. By using contemporary and objectively collected sodium purchase data, representative of Australian households, our findings suggest that differences in sodium consumption according to SES is likely at least partly driven by larger volumes of packaged foods and beverages purchased by lower-income households, rather than due to purchases of highersodium content products.…”
Section: Discussionmentioning
confidence: 59%